2022
DOI: 10.1101/2022.02.03.478996
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Beyond G1/S regulation: How cell size homeostasis is tightly controlled throughout the cell cycle?

Abstract: Proliferating cells require control mechanisms to counteract stochastic noise and stabilize the cell mass distribution in a population. It is widely believed that size-dependent timing of the G1/S transition is the predominant control process in mammalian cells. However, a model based only on such a checkpoint cannot explain why cell lines with deficient G1/S control are still able to maintain a stable cell mass distribution or how cell mass is maintained throughout the subsequent phases of the cell cycle. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 117 publications
(334 reference statements)
4
24
0
Order By: Relevance
“…Increasing cell size results in large-scale remodeling of the proteome ( Lanz et al, 2022 ). Larger cells also have a lower protein synthesis rate per unit volume (hereby referred to as growth rate) ( Tzur et al, 2009 ; Cadart et al, 2018 ; Neurohr et al, 2019 ; Liu et al, 2022 ), so that it is unclear if the size-dependent remodeling of the proteome that we have recently reported ( Lanz et al, 2022 ) was due to changing growth rates or due to cell size per se . We therefore sought to determine if and how the cell’s growth rate contributes to proteome remodeling ( Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing cell size results in large-scale remodeling of the proteome ( Lanz et al, 2022 ). Larger cells also have a lower protein synthesis rate per unit volume (hereby referred to as growth rate) ( Tzur et al, 2009 ; Cadart et al, 2018 ; Neurohr et al, 2019 ; Liu et al, 2022 ), so that it is unclear if the size-dependent remodeling of the proteome that we have recently reported ( Lanz et al, 2022 ) was due to changing growth rates or due to cell size per se . We therefore sought to determine if and how the cell’s growth rate contributes to proteome remodeling ( Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…One possibility for how cell size drives changes in protein concentrations would be that this is an indirect effect through the cell’s protein synthesis rate per unit volume (hereby referred to as growth rate), which decreases in larger cells ( Cadart et al, 2018 ; Neurohr et al, 2019 ; Liu et al, 2022 ) ( Figure 1B ). There seems to be a limit to the size range of effective biosynthesis, with larger cells exhibiting a loss of mitochondrial membrane potential ( Miettinen and Björklund, 2016 ) and reduced proliferative capacity ( Demidenko and Blagosklonny, 2008 ; Cheng et al, 2021 ; Lengefeld et al, 2021 ; Wilson et al, 2021 ; Lanz et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…To control their size to be within a target range, proliferating cells can either regulate their growth such that larger cells grow slower, or they can link cell growth to progression through the cell division cycle [15][16][17][18][19] . Studies in cultured cells have now begun to elucidate some of the molecular mechanisms that are responsible.…”
Section: Introductionmentioning
confidence: 99%
“…A key discovery made here is the significant loss of dry mass in early mitosis. Importantly, a loss of dry mass in mitosis has been reported in adherent mammalian cells studied using QPM ( Liu et al, 2020 ; Liu et al, 2022 ), but the higher temporal resolution of our results enables us to examine this phenotype in more detail. However, our measurement approach decreased the duration of mitosis and cytokinesis, which could potentially influence the dry mass dynamics we observe in mitosis.…”
Section: Discussionmentioning
confidence: 82%
“…We found that buoyant mass accumulation rate is high from prophase to metaphase-anaphase transition, that is, early mitosis. In contrast, studies using QPM have suggested that dry mass does not accumulate in early mitosis ( Zlotek-Zlotkiewicz et al, 2015 ), or that cells may even experience a decrease in dry mass in early mitosis ( Liu et al, 2020 ; Liu et al, 2022 ). If cells actually lose dry mass in mitosis, this would indicate previously unrecognized compositional changes taking place in mitosis.…”
Section: Introductionmentioning
confidence: 95%